2014
DOI: 10.1155/2014/872795
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical and Immunohistochemical Analysis of the Stomach of Rhinella icterica (Anura, Bufonidae)

Abstract: The stomach of Rhinella icterica was analyzed at light microscopy, employing histochemical techniques, lectin histochemistry, and immunohistochemistry for identifying enteroendocrine cells (EC). Although the stomach was composed of fundic and pyloric regions, its wall is formed by mucosa, submucosa, muscularis, and serosa. The mucosa was lined by a simple columnar mucous epithelium, supported by loose connective tissue. Several tubular, simple glands were composed of mucous neck cells, containing oxynticopepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 46 publications
0
7
0
4
Order By: Relevance
“…In all postmetamorphic specimens studied so far there is certain regionalization in the tubular gastric glands, and it is common to find mucous cells in the duct, and the oxynticopeptic cells in the alveolar portion. Oxynticopeptic cells can be identified by the presence of acidophilic zymogen granules [38][39][40][41] as is the case for Chacophrys pierottii (froglets) and Lepidobatrachus spp. (larval and postmetamorphic stages).…”
Section: Microscopic Morphology Of the Anterior Segment Of The Gastromentioning
confidence: 99%
“…In all postmetamorphic specimens studied so far there is certain regionalization in the tubular gastric glands, and it is common to find mucous cells in the duct, and the oxynticopeptic cells in the alveolar portion. Oxynticopeptic cells can be identified by the presence of acidophilic zymogen granules [38][39][40][41] as is the case for Chacophrys pierottii (froglets) and Lepidobatrachus spp. (larval and postmetamorphic stages).…”
Section: Microscopic Morphology Of the Anterior Segment Of The Gastromentioning
confidence: 99%
“…The oesophagus of I. supachaii is lined by pseudostratified ciliated columnar epithelium with different cell types, a typical characteristic of the oesophagus found in three amphibian orders (Norris 1959;Suganuma et al 1981;Setoguti et al 1987;Gallego-Huidobro et al 1992;Delsol et al 1995;Gallego-Huidobro and Pastor 1996;Junqueira et al 1999;Ferri et al 2001;Liquori et al 2002Liquori et al , 2005Liquori et al , 2007Exbrayat and Estabel 2006;Machado-Santos et al 2014). In addition, high vascularization at the subepithelial region of I. supachaii oesophagus may supply oxygen to the epithelial cells for their cellular respiration, thus providing energy and driving cellular activities, such as ciliary movement and exocytosis of the mucus.…”
Section: Discussionmentioning
confidence: 97%
“…However, the intestinal folds of I. supachaii are structurally different from the avian and mammalian villi of which the lamina propria possesses the central lacteal and the base leads into the intestinal tubular glands (crypts of Lieberk€ uhn; Andrew and Hickman 1974;Ishikawa et al 1985;Chikilian and de Speroni 1996;Reynolds and Rommel 1996;Zaher et al 2012) Mucosubstances are present throughout the digestive tract of I. supachaii from the oral cavity to the intestine, as described in this study, and in the cloaca, as reported in previous studies (Pewhom et al 2015(Pewhom et al , 2016. The distribution patterns of glycoconjugates along the digestive tract of I. supachaii exhibit regional variation and possibly interspecific variation, compared to other caecilians, including I. glutinosus (Zylberberg 1977), Caecilia gracilis, H. rostratus, M. unicolor, T. compressicauda (Exbrayat 1996(Exbrayat , 2003 (Zylberberg 1977), Hyla japonica, Pelophylax nigromaculatus (formerly Rana nigromaculata), Xenopus laevis (Suganuma et al 1981), R. aurora aurora (Ferri et al 2001), P. viridis and Rana temporaria (Liquori et al 2002) and Rhinella icterica (Machado-Santos et al 2014); and urodeles, including Calotriton asper (formerly Euproctus asper), Lissotriton helveticus, Pleurodeles waltii, Salamandra salamandra, Triturus cristatus, T. marmoratus (Zylberberg 1977), Ambystoma mexicanum (Suganuma et al 1981) and T. carnifex (Liquori et al 2007). In general, these mucosubstances serve to lubricate the digestive lumen, thus allowing smooth passage for food and protecting the mucosal surfaces from mechanical abrasion (Gallego-Huidobro et al 1992).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several animal studies on the distribution patterns of endocrine cells in the digestive tract were reported, including Tragulus javanicus [ 11 ], Babyrousa ­babyrussa [ 12 ], Manis javanica [ 13 ], Muntiacus muntjak [ 14 ], Rhinella icterica [ 15 ], and Hystrix javanica [ 16 ]. Regarding reptiles, almost all previous studies were reported on small reptiles such as Gekko japonicus , Eumeces chinensis , Sphenomorphus indicus , Eumeces elegans [ 17 ], and Tropidurus torquatus [ 18 ].…”
Section: Introductionmentioning
confidence: 99%